PEMBAHARUAN ISLAM ABUL KALAM AZAD DI INDIA - Patimah, Siti Husnul (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2019)
Islamic renewal is a renewal movement that aims to renew or provide understanding to Muslims about understanding Islam in terms of understanding in accordance with the teachings of Muslims. There are several figures in Islamic renewal, one of which is Abul Kalam Azad in India. The emergence of renewal carried out by Abul Kalam Azad that is due to the decline of Muslims. This article is an explanation of how the renewal was carried out by the figure of Abul Kalam Azad.